BORON REMOVAL FROM METALLURGICAL GRADE SILICON USING A FeCl2 MOLTEN SALT REFINING TECHNIQUE - Wu, Jijun; Jia, Binjie; Ma, Weihui; Yang, Bin; Liu, DaChun; Dai, Yongnian (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The slag refining for boron removal from metallurgical grade silicon is a promising metallurgical process for producing solar grade silicon. In this paper, FeCl2 molten salt has been used as a new refining agent to remove boron from MG-Si. The effects of refining time and mass ratio of MG-Si to molten salts on boron removal has been investigated in detail. The results showed that boron can be efficiently removed as the gaseous boron chloride and the boron concentration in MG-Si was successfully reduced from 22×10-6 to 4×10-6 at 1823K for 2 h with the mass ratio of MG-Si to FeCl2 molten salt of 1.0. The thermodynamic equilibrium process and the mechanism of boron removal were speculated and analyzed, respectively. The rate equation of boron removal was proposed and established in kinetic, which showed a large difference in removal limitation of boron compared with the results calculated in thermodynamic.